O PROTAGONISMO FEMININO NAS OBRAS LITERÁRIAS INFANTIS BOLIVIANAS - TARISSA MARQUES RODRIGUES (2024)
The thesis is part of the research line "Formative Processes, Educational Practices, and Differences", associated with the Research Group Studies and Research in Development, Gender, and Education (GEPDGE), under the Graduate Program in Education at the Faculty of Education, Federal University of Mato Grosso do Sul. The general objective of the research is to analyze how femininities are constructed and produced in children’s books within Bolivian literature. The specific objectives are: to identify the constitution of femininities in female characters in children’s books from Bolivian literary collections and to collect and group children’s books according to the gender conceptions they construct and produce. Thus, the children’s books were selected and analyzed based on the theoretical framework of gender studies and the discussions developed throughout the research.To underpin the analysis of discourses, the study employs the theoretical contributions of authors who discuss Gender, Feminist Studies, and Gender Studies from a post-structuralist perspective (Foucault, Deleuze, Butler, Louro, Xavier Filha, among others), as well as Feminism in Bolivia and identities (Paredes, Cândia, Galindo, Arroyo, Bhabha, Mignolo, among others). Furthermore, it draws on Literature Studies (Cândido, Colomer, Cosson, Coelho, Zilberman, Gisbert, Montoya, Reyes, Andruetto, Lajolo, among others) to reflect on the concepts and aspects generated during the development of the thesis.The methodology adopted qualitative research procedures, employing investigative instruments to conduct an in-depth analysis of the discursivities present in Bolivian children’s books. A total of 10 works were analyzed, all from the collection of the Bolivian Academy of Children’s and Youth Literature, selected based on their representativeness and recurrence of gender and femininity themes in female characters. The study aimed to identify and categorize the different forms of representation of feminine identities. A documentary and bibliographic analysis of the literary texts was conducted, employing analytical techniques using Foucauldian concepts, in accordance with approaches proposed by Foucault. These texts were categorized into four Foucauldian concepts of discourse: Power, Biopolitics, Genealogy, and Archeology, to explore how these texts not only tell stories but also produce forms of knowledge and power that shape identities, behaviors, and social values from childhood.The results highlight that Bolivian children’s literature is a powerful cultural artifact that significantly contributes to demystifying the gender prejudices historically rooted in society and schools. The analyzed cultural artifacts present diverse types of femininities, challenging stereotypes and allowing children to explore gender identities in a broader and more critical manner. By bringing these diverse femininities into the school space for debate, the study suggests they can foster a more inclusive and questioning understanding of gender roles in society.